2021
DOI: 10.14334/jitv.v26i1.2670
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Virgin Coconut Oil in Wistar Rats Infected with Staphylococcus aureus

Abstract: <p class="abstrak1">Virgin coconut oil (VCO) contains bioactive that induce immunity against infectious diseases. This study aim to determine the immunomodulatory effects of VCO based on the activity of superoxide dismutase (SOD), lymphocyte proliferation, and histopathological examination in liver and kidney of rats infected with <em>Staphylococcus</em> <em>aureus</em>. The VCO was given intragastrically to rats with a dose of 250 µL for one week. The rats were infected with <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…As is well known, Virgin coconut oil (VCO) contains active ingredients that can increase the body's immunity against disease agents. Research conducted by Widianingrum et al showed that VCO has the potential as an immunomodulator [32].…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, Virgin coconut oil (VCO) contains active ingredients that can increase the body's immunity against disease agents. Research conducted by Widianingrum et al showed that VCO has the potential as an immunomodulator [32].…”
Section: Resultsmentioning
confidence: 99%
“…Beberapa di antaranya yaitu optimalisasi dengan sistem integrasi sumber pakan lokal (Indrayani & Hellyward, 2015), peningkatan teknologi (Andria, Effendi, & Maesya, 2017;Purwantini, 2015), pola kemitraan (Pramita, Kusnadi & Harianto, 2017), optimasi wilayah dengan populasi tinggi (Dewi & Subagja, 2015), peningkatan usaha peternakan di wilayah strategis lain (Darsono, Putri, & Nahrowi, 2016;Yuniar, Fuah, & Widiatmaka, 2016). Strategi praktis guna meningkatkan kesehatan dapat dilakukan dengan cara perbaikan manajemen kesehatan termasuk di dalamnya kebersihan kandang, kontrol penyakit, program vaksinasi, pemberian fitobiotik sebagai imunomodulator alami (Khasanah, Silaban, Priyono, 2021;Widianingrum & Salasia, 2021).…”
Section: Animalunclassified
“…In the present study, we tried to apply nanotechnology to the natural ingredients of virgin coconut oil (VCO). VCO has enormous potential to be developed in the field of animal husbandry as a feed supplement (Widianingrum https://doi.org/10.17221/57/2022-VETMED et al 2019a), an antimicrobial (Widianingrum et al 2019b), and an immunomodulator (Widianingrum and Salasia 2021). The medium-chain fatty acid (MCFA) content is known to have an essential role in the various action mechanisms of VCO as a multifunctional drug (Tangwatcharin and Khopaibool 2012;Zentek et al 2013;Enig 2019) and can be used as an alternative to antibiotics.…”
mentioning
confidence: 99%
“…2019a ), an antimicrobial ( Widianingrum et al. 2019b ), and an immunomodulator ( Widianingrum and Salasia 2021 ). The medium-chain fatty acid (MCFA) content is known to have an essential role in the various action mechanisms of VCO as a multifunctional drug ( Tangwatcharin and Khopaibool 2012 ; Zentek et al.…”
mentioning
confidence: 99%